Changes in the main abilities of field hockey players during the preparatory period leading up to the main competition - Strzelczyk, R.; Konarski, J.; Karpowicz, K.; Janowski, J. (Acta Universitatis Palackianae Olomucensis. Gymnica, 2001)
These changes, which lead to the competitors attaining competition norms, will be accompanied by a suitable (stable or lowered) level of lactic acid. It has also been assumed that the changes, resulting from this structured training during the pre-Olympic training cycle (1999), will form the basis for possible changes in the 2000 Olympic training cycle.